TEACHING HIGH SCHOOL STUDENTS TO SOLVE DIFFERENTIAL EQUATIONS USING PYTHON AT MATH CLASS - Alkhan, K.B.; Shaimova , Z.E. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article discusses examples of the differential equation problem in Python with a graph for high school students. The basic characteristics of some tools for solving problems in mathematics using information technology are given. The difference between the two modern-known computer programs Python and Pascal is briefly explained. The article uses illustrative examples of built-in and manually entered functions that can be repeated by readers in Python to recreate graphs of trigonometric, differential, and other functions. In conclusion, it describes how the program can save time and energy for solving graphic problems in mathematics using the Python program. The article concludes that it is important for students to use logic to solve problems with improvised tools, where there are built-in functions, compared to remembering programming language algorithms for solving problems.